(untitled) (Comprehensive Journal of Science, 2026)
Ali Khalifa Al-Zaidi is regarded as one of the most prominent figures in the history of the Libyan Scout movement. He was born in the city of Al Khums, Libya, in 1909. At an early age, he left his homeland, as his family lived in exile in Lebanon to escape the oppression of Italian Colonial Rule in Libya. During this period abroad, he received his early education and acquired his first experiences in the Scout movement, experiences that later played a crucial role in shaping his educational vision and methodological approach to youth development. Upon his return to Libya in the early 1950s, Al-Zaidi founded the national Scout movement in 1954. He undertook the organization of Scout groups, the development of their training and educational programs, and the preparation of competent national cadres capable of leading youth initiatives. His leadership was distinguished by a strong educational orientation toward both Scouts and Guides, emphasizing the cultivation of national values, the development of individual and social responsibility, and the strengthening of a sincere sense of belonging to the homeland. Furthermore, Al-Zaidi made a significant contribution to consolidating the position of the Scout movement among Libyan youth. Through his efforts, the movement became an influential educational and social institution, which established him as a symbol of national Scout leadership and a foundational reference in the establishment and development of the Scout movement within Libyan society.